Theory of ultrafast autoionization dynamics of Fano resonances - Chu, W.-C.; Lin, C. D. (My University, 2010)
We study atomic autoionization processes in the time domain. With the emerging attosecond extreme vacuum ultraviolet and soft x-ray pulses, we first address how to characterize the time evolution of the decay of a discrete state into a degenerate continuum. A short pump beam generates a number of resonance states in a series and the nearby background continuum, and the resultant wave packet evolves with time until the full decay of the bound states. Taking the 2pns(1Po) resonance series embedded in the 2sεp(1Po) continuum in a beryllium atom as an example, the time evolution of the autoionizing wave packet in the energy domain and in coordinate space is calculated and analyzed, where Fano profiles build up in the photoelectron energy during the process. A proposed pump-probe scheme assumes that the probe beam ionizes the 2s inner electron in the wave packet. The lifetimes of the resonances and the photoelectron energy distribution can be obtained from the ionization yield vs. the time delay of the probe.